Comparative effectiveness of topical lignocaine nebulization and airway nerve blocks for awake fiber-optic nasal intubation in TM joint ankylosis - Mohammad Sadiq Malla (Manipal College of Medical Sciences, Pokhara, 2021)
Background: Awake fiber-optic nasal intubation is a gold standard management of difficult airway in temporal mandibular (TM) joint ankylosis.